The Covid-19 Pandemics: why Intersectionality Matters - Maestripieri, Lara (Frontiers in Sociology, 2021)
Covid-19 has been a disrupting event in contemporary social life but is far from being a great equaliser. Preliminary studies have put in evidence how different social groups faced a differentiated risk of contagion and coped differently with the various consequences of the emergency. Evidence shows how minorities and migrants face disproportionally higher risks of contagion than the white upper and middle class, and how vulnerable communities are more exposed to deaths and the rapid spread of the virus. At the same time, societies are coping with social distancing measures and their disruptive social and economic consequences, which have a more significant impact on the most vulnerable segments of societies: women, children, low-income classes and ethnic minorities. This article argues that an intersectional framework allows an understanding of what is occurring in the current pandemic, both in terms of its social determinants and social consequences. To open the black box of inequality, intersectional scholars analyze the intersections of multiple structures of inequalities (such as gender, age, class, ethnicity), which have a multiplying effect when disadvantaged positions intersect in the same individual. Covid-19 is a clear example of an intersectional phenomenon: the impact of individual and community exposure to Covid-19 is the results of multiple and interrelating structures of inequality. Up to now, research in social sciences has underestimated the role of intersectionality in analyzing the social and economic consequences of this pandemic.